2013
DOI: 10.3390/ijms14059062
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and Genetic Differentiation among Populations of the Moon Turban Snail Lunella granulata Gmelin, 1791 (Gastropoda: Turbinidae)

Abstract: We examined the genetic variation and phylogeographic relationships among 10 populations of Lunella granulata from mainland China, Penghu Archipelago, Taiwan Island, and Japan using mitochondrial COI and 16S markers. A total of 45 haplotypes were obtained in 112 specimens, and relatively high levels of haplotype diversity (h = 0.903) and low levels of nucleotide diversity (π = 0.0046) were detected. Four major phylogenetic lineage clusters were revealed and were concordant with their geographic distribution, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 62 publications
2
21
0
2
Order By: Relevance
“…, ), the moon turban snail Lunella granulata (Chiu et al. ), and the intertidal snail Batillaria attramentaria (Kojima et al. ), our present study demonstrates the importance of the climate changes since the Late Pleistocene and the diversifying effect of the regional and ocean currents to both the demography and genetic differentiation of gastropods in this region.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…, ), the moon turban snail Lunella granulata (Chiu et al. ), and the intertidal snail Batillaria attramentaria (Kojima et al. ), our present study demonstrates the importance of the climate changes since the Late Pleistocene and the diversifying effect of the regional and ocean currents to both the demography and genetic differentiation of gastropods in this region.…”
Section: Discussionsupporting
confidence: 60%
“…, , ; Chiu et al. ; Xue et al. ) as a common effect of past climate changes on marine species, as in other oceans (Table and references therein, Grant et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the Pattern in the waters of Cendrawasih Bay which has semienclosed characteristics that minimize the potential input of gene variations from outside these waters. Chiu et al (2013) state that genetic diversity can be determined by two main factors, namely, habitat condition and excessive exploitation. Based on the observations conducted by Limpus, (1997) he stated that most marine turtle populations in the Indo Pacific Region experienced a Himawan et al (2015), the unique characteristics of marine species found in Cendrawasih Bay are not the same and not even found in other regions.…”
Section: Discussion 321 Genetic Diversitymentioning
confidence: 99%
“…Riau Islands are close to the South China Sea and Tanimbar Islands are located adjacent to Arafuru Sea. The existence of strong current in locations adjacent to high seas allows the connectivity process in biodiversity (Chiu et al 2013).…”
Section: Species Distribution and Seagrass Conditionsmentioning
confidence: 99%